Muscle contractile properties and perceived fatigue in the general and diseased population - Isa H. Mast; Neeltje A. E. Allard; Dominique tenHaaf; Anouk A. F. Stoffels; Lando Janssen; Hieronymus W. H. vanHees; Silvie Timmers; Bregina T. P. Hijmans‐Kersten; Maria T. E. Hopman; Laurien M. Buffart (Physiological Reports)
Abstract Knowledge of muscle contractile properties, physical fitness, and their associations with perceived fatigue may provide insights into mechanisms inducing fatigue and treatment targets. We aimed to identify differences in contractile properties and physical fitness between populations, and examine associations with perceived fatigue. We pooled data on perceived fatigue, physical fitness, and contractile properties from six studies, including a control group (n = 90), cancer survivors (n = 27), patients with chronic obstructive pulmonary disease (COPD; n = 16), chronic myeloid leukemia (CML; n = 20), and statin users (n = 64). We evaluated differences between populations, and associations of contractile properties and physical fitness with perceived fatigue. Compared with the control group, we found differences in contractile properties of patients with COPD (larger muscle force decline: β = −10.5%, 95% CI = −16.7; −4.2, increase in early relaxation time (Rt): β = 84.4%, 95% CI = 51.7; 117.0, increase in half Rt: β = 83.1%, 95% CI = 45.5; 120.7, muscle force rise (MFR): β = 0.2%/ms, 95% CI = 0.1; 0.3, and decrease in MFR: β = −24.3%, 95% CI = −35.7; −13.0) and statin users (early Rt: β = −5.4 ms, 95% CI = −10.0; −0.8, increase in early Rt: β = 19.8%, 95% CI = 2.5; 37.1). Associations between contractile properties and perceived fatigue varied across populations. Longer relaxation times were associated with higher perceived fatigue in hemato‐oncological populations. To conclude, contractile properties were impaired in patients with COPD and statin users. Associations between contractile properties and perceived fatigue varied across populations. In hemato‐oncological populations, impaired muscle relaxation was associated with higher perceived fatigue.